Validity of the Mini‐BESTest in adults with myotonic dystrophy type 1. Issue 1 (3rd May 2020) - Duchesne, Elise; Hébert, Luc J.; Mathieu, Jean; Côté, Isabelle; Roussel, Marie‐Pier; Gagnon, Cynthia
Abstract: Introduction: Myotonic dystrophy type 1 (DM1) is a multisystemic neuromuscular disease that causes balance problems. The objective of this study was to assess the construct validity of the Mini‐BESTest among adults with DM1. Methods: Fifty‐nine individuals with late‐onset or adult phenotypes of DM1 were recruited. Participants performed the Mini‐BESTest, 10‐Meter Walk Test (10mWT), 6‐Minute Walk Test (6MWT), and Timed Up & Go (TUG) and were questioned on their tendency to lose balance and whether they fell in the past month. Results: Scores on the Mini‐BESTest were significantly different between phenotypes and CTG repeat numbers ( P  < .02). Significant correlations were found with the 10mWT, 6MWT, and the TUG ( r = 0.77–0.84; P  < .001). A cutoff score of 21.5 was found to identify fallers with 90% posttest accuracy. Discussion: The Mini‐BESTest demonstrates evidence of construct validity when assessing balance in the DM1 population.